Effect of human milk enriched with human milk-based fortifier (HMBF) versus bovine milk-based fortifier (BMBF) on growth and morbidity among very low birth weight (VLBW) infants – A randomized controlled trial - Rakesh Kotha (Hygeia Press di Corridori Marinella, 2021)
Introduction: Survival of preterm neonates increased dramatically with the advancement in neonatology services. These infants have high nutritional demands for optimal growth, and human milk alone is insufficient to meet their needs. Hence, fortification of milk has become the standard of care. Bovine milk-based fortifiers (BMBF) are commonly used, but there exists concern regarding the exposure to cow milk protein. Human milk-based fortifier (HMBF) use offers a theoretical advantage from the immunological and gastrointestinal standpoint. We intend to study the effects of HMBF compared to BMBF on growth and morbidity of preterm neonates.